Antibacterial Activity Test of Noni Leaves (Morinda citrifolia L.) Ethanol Extract Ointment Against Staphylococcus aureus Bacteria - Arifin, Arfiani; Djide, Natsir; Muhtar, Mardiyana (Sanata Dharma University, 2024)
Noni leaves (MorindacitrifoliaL.) are known to provide antibacterial properties and can be used in ointment formulations to prevent or eliminate germs that might cause infections, such as Staphylococcus aureus. This research aimedto formulate an ointment containing noni leaf ethanol extract that fulfills the physical quality test standards and to determine the antibacterial activity of various concentrations of ethanol extract of noni leaves in ointment preparations against Staphylococcus aureus bacteria. The extraction technique employed was maceration with 96% ethanol. The extracted substance was formulated into ointments with concentrations of 2.5%, 5%, and 10%. The antibacterial activity of the ointment was evaluated using the agar diffusion method with wells. Organoleptic, homogeneity, pH, spreadability, and adhesion tests demonstrated that the ointment at the three concentrations of 2.5%, 5%, and 10% satisfied the physical quality test standards. The antibacterial activity test revealed that a 96% ethanol extract of noni leaves inhibited the growth of Staphylococcus aureus bacteria with the maximum diameter of the inhibition zone at a concentration of 10% (15.26 mm) and was classified as strong.